Melancolia e resistência: em câmara lenta - PINHEIRO, Veridiana Valente (Universidade Federal do Pará, 2020)
Aiming to observe some historical and cultural resonances of 1964 Brazilian Military Dictatorship, this work parts from the relation between literature and cinema and its effects in the composition of novel Em camera lenta (1977), by the Brazilian writer Renato Tapajós.